Teaching Trauma Theory and Practice in Counselor Education: A Multiple Case Study - Charmayne R Adams; Casey A Barrio Minton; Jennifer Hightower (Teaching and Supervision in Counseling, 2023)
Teaching about trauma theory and practice is an integral part of counselor preparation. The purpose of this multiple case study was to understand how counselor educators (CEs) designed and facilitated significant learning experiences regarding trauma theory and practice. The researchers aimed to answer two research questions (1.) how do CEs choose which content to address in trauma courses and (2.) which teaching methods do CEs use to facilitate significant learning experiences in trauma courses? The study participants were three CEs teaching trauma courses in multiple formats (face-to-face, online, and hybrid) in CACREP programs. The results indicated that instructors faced unique situational factors that impacted their choice of teaching and learning activities and assessment measures. The themes Instructor Role, Instructor Identity, and Eliciting Fundamental Change in Learners impacted which teaching methods were chosen to facilitate significant learning experiences. The manuscript includes implications for CEs designing and teaching trauma courses.
Keywords: Counselor Education; Trauma; Multiple Case Study